Testing of Braden QD Scale for predicting pressure ulcer risk in the Pediatric Intensive Care Unit - Puspitasari, Jayanti Dwi (Pediatr Rep, 2020)
Children admitted to the Pediatric Intensive Care Unit (PICU) are at risk for pressure injury due to immobility and the challenge of positioning medical devices. However, a comprehensive instrument to assess pressure injury risk is still finite. This study aimed to test the validity and reliability of the Braden QD Scale. The design used was a Pearson correlation coefficients and Cronbach’s alpha (α). Fifty-one pediatric patients below age 18 who had been bedridden for at least 24 hours were engaged through a consecutive sampling method. The results showed assessments made by using the Braden QD Scale revealed that 88.2% of patients were at risk for a pressure injury. The validity test results of the Braden QD Scale ranged between 0.532 and 0.833. The reliability test results of the Braden QD Scale ranged between 0.756 and 0.834. The sensitivity value is 100%, specificity value is 40%. In general, the study finding suggests that the Braden QD Scale is a valid and reliable instrument for predicting pressure injury risk. Nurses may employ this tool to assess pressure injury risk in pediatric patients.